Incident depression and mortality among people with different types of dementia: results from a longitudinal cohort study - Perna, Laura; Wahl, Hans-Werner; Mons, Ute; Schöttker, Ben; Brenner, Hermann (Social psychiatry and psychiatric epidemiology, 2019)
PURPOSE: The aim of this study was to investigate the independent and combined association of incident depression and dementia with mortality and to explore whether the magnitude of the association varies according to different types of dementia, including Alzheimer's disease and vascular dementia. - METHODS AND DESIGN: The study was based on a population-based longitudinal cohort consisting of 9940 participants at baseline and followed for over 14 years. The sample used for the analyses included 6114 participants with available information on diagnosis of incident dementia and depression. For survival analyses, Cox regression models with incident dementia (n = 293; 5%) and incident depression (n = 746; 12%) as time-dependent variables were used. - RESULTS: Cox models adjusted for relevant confounders indicated that comorbidity of incident vascular dementia and incident depression was associated with a much higher mortality risk (HR 6.99; 95% CI 3.84-12.75) than vascular dementia in the absence of depression (HR 2.80; 95% CI 1.92-4.08). In contrast, estimates for comorbidity of Alzheimer's disease and depression were slightly lower than those for Alzheimer in absence of depression (HR 3.56; 95% CI 1.83-6.92 and HR 4.19; 95% CI 2.97-5.90, respectively). Incident depression in the absence of incident dementia was only weakly associated with mortality. - CONCLUSIONS: These findings indicate that depression and vascular dementia might have synergistic effects on mortality. The results have relevant public health implications for prevention, routine screening for and early treatment of depression among older people, especially those at risk of vascular dementia.
Gesehen am 29.08.2019